KESENIAN RONGGIANG DALAM KARYA SENI LUKIS REALIS - Arnanda Sarisman, Drs. Abd. Hafiz, M.Pd. (Universitas Negeri Padang, 2019)
Ronggiang art is one of the traditional arts in the form of unrequited dance performances accompanied by music, ronggiang usually performed at wedding, Eid al-Fitr, Eid al-Adha and other holidays. The purpose of making this work is to visualize the ronggiang art in realist painting in order to promote to the public that this art exists and should be preserved. The object of this work is related to musical instruments, dancers, and music players in ronggiang art. This final work consists of ten works with the titles: core I, core II, mairiang, gadih basanai, talatak, sarantak saayun, basingkadu, pandendang I, pandendang II and having fun together.Keywords: ronggiang, Painting, Realist.